Diagnostic and Predictive Value of Immune-Related Genes in Crohn’s Disease - Yu, Bing; Yin, Yi-xin; Tang, Yan-ping; Wei, Kang-lai; Pan, Zhi-gang; Li, Ke-Zhi; Guo, Xian-wen; Hu, Bang-li (Frontiers in Immunology, 2021)
Abnormal immune cell infiltration is associated with the pathogenesis of Crohn’s disease (CD). This study aimed to determine the diagnostic and predictive value of immune-related genes in CD. Seven Gene Expression Omnibus datasets that analyzed the gene expression in CD tissues were downloaded. Single-sample gene set enrichment analysis (ssGSEA) was used to estimate the infiltration of the immune cells in CD tissues. Immune-related genes were screened by overlapping the immune-related genes with differentially expressed genes (DEGs). The protein-protein interaction (PPI) network was used to identify key immune-related DEGs. Diagnostic value of CD and predictive value of anti-TNFα therapy were analyzed. Immunohistochemical (IHC) assay was used to verify gene expression in CD tissues. There were significant differences among CD tissues, paired CD tissues, and normal intestinal tissues regarding the infiltration of immune cells. AQP9, CD27, and HVCN1 were identified as the key genes of the three sub-clusters in the PPI network. AQP9, CD27, and HVCN1 had mild to moderate diagnostic value in CD, and the diagnostic value of AQP9 was better than that of CD27 and HVCN1. AQP9 expression was decreased in CD after patients underwent anti-TNFα therapy, but no obvious changes were observed in non-responders. AQP9 had a moderate predictive value in patients who had undergone treatment. IHC assay confirmed that the expression of AQP9, CD27, and HVCN1 in CD tissues was higher than that in normal intestinal tissues, and AQP9, CD27 was correlated with the activity of CD. Immune-related genes, AQP9, CD27, and HVCN1 may act as auxiliary diagnostic indicators for CD, and AQP9 could serve as a promising predictive indicator in patients who underwent anti-TNF therapy.